If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -11 = x + 21 Reorder the terms: -11 + 3x = x + 21 Reorder the terms: -11 + 3x = 21 + x Solving -11 + 3x = 21 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -11 + 3x + -1x = 21 + x + -1x Combine like terms: 3x + -1x = 2x -11 + 2x = 21 + x + -1x Combine like terms: x + -1x = 0 -11 + 2x = 21 + 0 -11 + 2x = 21 Add '11' to each side of the equation. -11 + 11 + 2x = 21 + 11 Combine like terms: -11 + 11 = 0 0 + 2x = 21 + 11 2x = 21 + 11 Combine like terms: 21 + 11 = 32 2x = 32 Divide each side by '2'. x = 16 Simplifying x = 16
| 4+4b=34.4 | | 24=6+7x-5x | | 14x(5-6)= | | 2(y+1)=y-4 | | 2+6s=26 | | 9y-13y=-10-14 | | 19-12a=79 | | x^4-x^2-14x+54=0 | | 93.3=13b-10.7 | | 3x+5+4x=5 | | 4a-1=-37 | | g(0)=3x^2-2x | | 3+4x-18= | | 2-5x=3x-14 | | -5(x-4)=0 | | -216+125x^3=0 | | x+x+1+x+2=90 | | 5(r-5)=2(r-4)-4 | | 3a-19=-49 | | 2(x-3)=34 | | 4x-23=3x-5 | | 6x+9-5x=12 | | 42a^4+60a^3=0 | | 5z+7=6(z-2)-4(2z-3) | | -39=6+5t | | 25x+5(x+5)+10(x-9)=3,115 | | 3(x)=18 | | (5x^4)(25x^2)= | | x+(x+2)+(x+4)=-17 | | I-4I= | | 2x-5=-4x-2 | | 3x-1=x+21 |